(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The aim of the current research is to explain the importance of engineering insuranrance as an independent variable With its dimensions represented by (pricing , compensation ,risks of engineering insurance, and technology ) and the degree to Which these dimensions are arranged according to their importance and priorities in ensuring the success the main question, which is :To what extent is the ability of the researched company aware of the importance of engineering insurance and its impact on investment projects ?The research was applied in the National insurance Company . The descriptive analytical approach was adopted , and the questionnaire was prepared in light of it as amain measuring tooi in obtaining data from the research community , relying on a purposive sample of (78) people in job positions (general manager , branch manager , department manager , division official ,and unit official ), and reliad on the statistical program (spss v28) to calculate the most notable of which are :Standard deviation , Coefficient of variation , regression Coefficient ar , test , F test )the arithmetic mean , and the research reached a number of results . • There is a positive correlation between engineering insurance and investment projects. • The compensation dimension is the dimension that has the most significant impact on investment projects.